Analisis Profil Protein Ekstrak Aquades dan Etanol Daun Mimba (Azadirachta Indica A. Juss) dengan Metode SDS-PAGE (Protein Profile Analysis of Aquadest and Ethanol Extract of Neem Leaves by Means of SDS-PAGE Method) - Miftah Dewi Masyitoh; I. D. A. Ratna Dewanti; Dyah Setyorini (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Background: Neem leaf is used to increase body imune response, antivirus, antifungi,antibacterial, dan antioxidant. These biology activities was suspected because of proteinin neem leaf. Protein in plants can be used as pharmacogenetic identification becausesome proteins in plants posse characteristic can defense to some pathogenmcroorganism. The way to know protein in the organism is using profile protein analyticthrough SDS-PAGE method. SDS-PAGE separates protein molecules by size andparticular shapping and also can determine protein molecular weight. Protein profilescan be obtained with protein extracts using solvents. Protein is a polar compound whichis bonded to a polar solvent therefore chosen ethanol and aquadest as a liquid asextraction solvent . Purpose: To know the protein profile of aquadest and ethanolextracts of neem leaf by using SDS-PAGE. Method: This study uses neem leaf as asample, aquadest and 70% ethanol as the extraction solvent then analyzed using SDSPAGE.Result: The results showed 9 protein bands on the aquadest extract of neemleaf and 8 of protein bands on the ethanol extract of neem leaf. Conclusion: From thestudy, there is a difference between the amount of protein bands aquadest extracts ofneem leaf with ethanol extract of neem leaf.Keywords: aquadest extract, ethanol extract, neem leaf, protein profile, SDS-PAGE